Combination of photothermia and magnetic hyperthermia properties of Fe3O4@Ag hybrid nanoparticles fabricated by seeded‐growth solvothermal reaction. Issue 4 (14th August 2021) - Linh, Nguyen Thi Ngoc; Tam, Le The; Nguyet, Ha Minh; Dung, Ngo Thanh; Du, Nguyen Hoa; Tam, Le Thi Thanh; Nam, Pham Hong; Vinh, Nguyen Dinh; Vuong, Nguyen Thien; Quang, Ngo Dai; Lu, Le Trong
Abstract: In this work, the monodisperse Fe3 O4 @Ag core‐shell hybrid nanoparticles (NPs) with an average size of 16.0 nm have been successfully fabricated by the seeded‐growth method in the organic solvent. The influence of the molar ratios of AgNO3 /OLA on the formation of hybrid NPs has been investigated in detail to find the optimal conditions for the synthesis of the desired Fe3 O4 @Ag hybrid NPs. The hydrophobic Fe3 O4 @Ag hybrid NPs were successfully transferred into the water using poly (maleic anhydride‐alt‐1‐octadecene) (PMAO). The PMAO coated Fe3 O4 @Ag nanoparticles were well dispersed and stable in water over a wide range of pH from 2 to 11 as well as reasonable electrolyte concentration. The Fe3 O4 @Ag magneto‐plasmonic design can efficiently combine magnetic hyperthermia into an effective bimodal thermo‐therapy.